A rare solid tumor of the retroperitoneum with venous extension and lung metastasis: Extra-gastrointestinal stromal tumor - Türker Acar; Duran Efe; Ahmet Okuş; İrfan Öcal and Mustafa Harman (Turkish Journal of Gastroenterology, 2019)
-